Pengaruh Layanan Penguasaan Konten dengan Teknik Psikodrama Terhadap Perilaku Prososial Siswa - Puspita, Regina Dewi; Hartati, Maria Theresia S. (Universitas Negeri Semarang, 2016)
This research has been implemented according to phenomenon in junior high shcool 2 Warureja which shows prosocial behavior of students is low shown by behavior less contribute to cooperative classroom and school, less able to help selflessly, honesty is still low. The purpose of this research was to know influence mastery of content services with psychodrama techniques on prosocial behavior by looking at difference before and after service. The research is experimental research design used is one group pre test-post test design. The population is all 7th grade students in Junior High School 2 Warureja with a total of 203 students and sample number of 20 students using purposive sampling technique. Prosocial scale instruments have been tested using the construct validity of product moment, and reliabelitas instrument with Alpha. Technique analyze data use the Wilcoxon matched pairs test. Test results obtained score t count = 0 < t table = 52, and z count = 3,919 > table z = 1.645, or means Ha accepted and Ho rejected. Results of this research is mastery content service with psychodrama techniques has positive effects on prosocial behavior 7th grade. Therefore, the results of this research can used to develop student prosocial behavior.